A novel spread spectrum underwater acoustic communication system for the inter-symbol interference reduction. (6th March 2023) - Li, Yan; Jia, Ning; Huang, Jianchun; Liu, Biao; Guo, Shengming
A novel spread spectrum Underwater Acoustic (UWA) communication system is proposed to suppress the Inter-Symbol Interference (ISI) caused by the long time-delay spread underwater acoustic multipath channels in this paper. The Interleaved Hybrid Spread Spectrum (IHSS) communication method is combined with M-ary code shift spread spectrum and interleaving method, which has an excellent communication performance when the time-delay spread of the UWA channels is larger than the period of pseudo-noise sequences in the spread spectrum system. The BER performance of the proposed system and the Conventional M-ary Code Shift Spread Spectrum underwater communication system (CMCSSS) is evaluated through computer simulations and the sea trial. The results demonstrate the proposed system can effectively suppress ISI and has a better communication quality.